2015
DOI: 10.1371/journal.pone.0140130
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Resistance between Cry1 Proteins in Fall Armyworm (Spodoptera frugiperda) May Affect the Durability of Current Pyramided Bt Maize Hybrids in Brazil

Abstract: Genetically modified plants expressing insecticidal proteins from Bacillus thuringiensis (Bt) offer valuable options for managing insect pests with considerable environmental and economic benefits. Despite the benefits provided by Bt crops, the continuous expression of these insecticidal proteins imposes strong selection for resistance in target pest populations. Bt maize (Zea mays) hybrids have been successful in controlling fall armyworm (Spodoptera frugiperda), the main maize pest in Brazil since 2008; howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
121
1
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 125 publications
(138 citation statements)
references
References 36 publications
11
121
1
5
Order By: Relevance
“…The nonrecessive resistance could be one of the reasons that led to the rapid development of resistance to the Cry1F maize in some field populations of S. frugiperda. Cross-resistance of Cry1F-resistant S. frugiperda to Cry1A.105 protein or Cry1A.105 maize has also been reported in two previous studies Bernardi et al, 2015); Cry1F and Cry1A.105 have similar structures and thus selection for resistance to one is expected to confer resistance to the other. A previous study also showed that Cry1A.105 resistance alleles in the field populations of S. frugiperda collected in 2011 from Florida, U.S. was relatively abundant, reached 0.056 with a 95% credibility interval of 0.032e0.087 .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The nonrecessive resistance could be one of the reasons that led to the rapid development of resistance to the Cry1F maize in some field populations of S. frugiperda. Cross-resistance of Cry1F-resistant S. frugiperda to Cry1A.105 protein or Cry1A.105 maize has also been reported in two previous studies Bernardi et al, 2015); Cry1F and Cry1A.105 have similar structures and thus selection for resistance to one is expected to confer resistance to the other. A previous study also showed that Cry1A.105 resistance alleles in the field populations of S. frugiperda collected in 2011 from Florida, U.S. was relatively abundant, reached 0.056 with a 95% credibility interval of 0.032e0.087 .…”
Section: Discussionsupporting
confidence: 65%
“…Relative to the single-gene Bt maize, these pyramided Bt maize products are usually more effective against some target pests, especially Noctuidae species such as the corn earworm (Helicoverpa zea [Boddie]) and S. frugiperda (Burkness et al, 2010;Niu et al, 2014;Yang et al, 2013Yang et al, , 2015. The widespread Cry1F resistance in S. frugiperda has sparked concerns about the durability of the pyramided Bt crops Bernardi et al, 2015;Santos-Amaya et al, 2015;Yang et al, 2016). One of the Bt proteins expressed in some pyramided Bt maize is Cry1A.105.…”
Section: Introductionmentioning
confidence: 99%
“…While, a few cases of study in laboratory and field populations showed that the insect could evolve resistance to pyramid crops (Bernardi et al, 2015;Brévault et al, 2013;Fabrick et al, 2015;Wei et al, 2015;Welch et al, 2015). However, study by who reported that the resistance to pyramids is due to similarity of amino acid sequence between Bt toxins, which affect the cross-resistance when the resistance is associated with mutations, that reduce binding to midgut receptor.…”
Section: Resistance To Pyramid Bt Cropsmentioning
confidence: 99%
“…Ocupando 45,7 milhões de hectares, mais de 90% da área total do país de soja, milho e algodão é semeada com culturas transgênicas que se tornaram a principal ferramenta para o manejo de insetos pragas e plantas daninhas (CELERES, 2016). No entanto, o plantio contínuo e sucessivo de extensas áreas com culturas que expressam genes de Bacillus thuringiensis Berliner tem acarretado em intenso processo de seleção e evolução de populações de pragas resistentes (FARIAS et al, 2013;BERNARDI et al, 2015;OMOTO et al, 2016). No Brasil, trinta e três eventos que expressam proteínas Bt para o controle de insetos são autorizados para o plantio comercial (CTNBIO, 2016).…”
Section: Introductionunclassified
“…Entretanto, diversos autores têm demonstrado que estas mudanças temporais e espaciais na paisagem têm contribuído para o aumento populacional de pragas polífagas (MATSON et al, 1997;BIANCHI et al, 2003BIANCHI et al, , 2006MARTINELLI et al, 2006MARTINELLI et al, , 2007FARIAS et al, 2014;BERNARDI et al, 2015). A habilidade de H. armigera em colonizar diversos hospedeiros simultaneamente em diferentes regiões ao longo do ano é reconhecida como o principal fator que define o tamanho e a manutenção populacional (PASHLEY, 1988;FITT, 1989;NAGOSHI;MEAGHER, 2008).…”
Section: Introductionunclassified